Характеристика методів технічної експертизи паспорта громадянина України, що містить безконтактний електронний носій із біометричними даними власника - Безсонна, Т. Ф.; Bezsonna, T. F.; ORCID: http://orcid.org/0000-0002-2482-9564 (Юридична наука. - 2019. - № 11 (101), т. 2. - С. 120-128, 2019)
Виокремлено, упорядкувано та описано методи, що використовуються спеціально уповноваженою особою в ході провадження технічної експертизи паспорта громадянина України, що містить безконтактний електронний носій із біометричними даними його власника.

The use of specialized knowledge in criminal proceedings is an integral part of a full, objective and impartial investigation of criminal offenses. The most common form of their use is forensic examination. There is a procedural procedure for their appointment, conduct and registration of results. At the heart of all expert research is a clear technological process, the implementation of which would be impossible without the use of general scientific, separate scientific or general expert methods. The latter must be substantiated in nature, meet the norms of various spheres of human existence and effective tools to achieve this goal. The purpose of the article is to identify, organize and describe the methods used by a specially authorized person during the technical examination of the passport of a citizen of Ukraine, which contains contactless electronic media with biometric data of its owner. The article highlights the concept of forensic examination of documents. The content of the method of expert research in a broad and narrow aspects is revealed. A number of classification requirements proposed by forensic scientists are given. The own vision of grouping of methods of technical and criminalistic research of the passport of the citizen of Ukraine containing the contactless electronic carrier with biometric data of the owner of the document is offered. Each of the proposed methods is described. It is noted that the methods of forensic examination of biometric passports meet certain criteria such as: legality, scientific validity, technicality, efficiency and safety of the document. It has been found that the method of holographic examination is considered to be highly sensitive, which consists in the examination by a forensic expert of the font available in the document submitted for examination. It helps to solve diagnostic problems and to identify the type or variety of device with which the typewriter was written or a protective image was applied. With the help of this method you can explore the relief image of the passport holder, protective nets, stylized images of the flag and small coat of arms of Ukraine with three levels of authentication (animation effect due to the rotation of the document), etc.

Выделены, упорядочены и описаны методы, используемые специально уполномоченным лицом в ходе проведения технической экспертизы паспорта гражданина Украины, содержащей бесконтактный электронный носитель с биометрическими данными его владельца.
Characteristics of methods of technical examination of the passport of the citizen of Ukraine, which contains contactless electronic media with biometric data in
Безсонна, Т. Ф. Характеристика методів технічної експертизи паспорта громадянина України, що містить безконтактний електронний носій із біометричними даними власника / Безсонна Т. Ф. // Юридична наука. - 2019. - № 11 (101), т. 2. - С. 120-128.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Криміналістика. Criminalistics. Криминалистика; Україна. Ukraine. Украина; кримінальне провадження; criminal proceedings; уголовное производство; метод експертного дослідження; method of expert research; метод экспертного исследования; біометричний паспорт; biometric passport; биометрический паспорт; технічна експертиза документів; technical examination of documents; техническая экспертиза документов; біометричні дані; biometric data; биометрические данные; безконтактний електронний носій; contactless electronic media; бесконтактный электронный носитель